All our trials: prisons, policing, and the feminist fight to end violence - Thuma, Emily L. (Women, gender, and sexuality in American history, 2019)
Introduction -- Lessons in self-defense: from "free Joan Little" to "free them all" -- Diagnosing institutional violence: forging alliances against the "prison/psychiatric state" -- Printing abolition: the transformative power of women's prison newsletters -- Intersecting indictments: coalitions for women's safety, racial justice, and the right to the city -- Epilogue